Microsurgical anatomy of the infratemporal fossa. Issue 4 (27th January 2013) - Joo, Wonil; Funaki, Takeshi; Yoshioka, Fumitaka; Rhoton, Albert L.
Abstract: The objective of this study is to clearly and precisely describe the topography and contents of the infratemporal fossa. Ten formalin‐fixed, adult cadaveric specimens were studied. Twenty infratemporal fossa were dissected and examined using micro‐operative techniques with magnifications of 3–40×. Information was obtained about the inter‐relationships of the contents of the infratemporal fossa. The infratemporal fossa lies at the boundary of the head and neck, and the intracranial cavity. It is surrounded by the maxillary sinus anteriorly, the mandible laterally, the pterygoid process anteromedially, and the parapharyngeal space posteromedially. It contains the maxillary artery and its branches, the pterygoid muscles, the mandibular nerve, and the pterygoid venous plexus. The course and the anatomic variation of the maxillary artery and the branches of the mandibular nerve were demonstrated. The three‐dimensional (3D) relationships between the important bony landmarks and the neurovascular bundles of the infratemporal fossa were also shown. The skull base anatomy of the infratemporal fossa is complex, requiring neurosurgeons and head and neck surgeons to have a precise knowledge of 3D details of the topography and contents of the region. A detailed 3D anatomic knowledge is mandatory to manage benign or malignant lesions involving the infratemporal fossa without significant postoperative complications. Clin. Anat., 2013. © 2013 Wiley Periodicals, Inc.